Features of myometrium remodeling after surgical inteventions on the uterus - Zhelezov, D. M.; Kossey, T. V.; Zarzhitskaya, N. A. (Journal of Education, Health and Sport, 2020)
Introduction. Recently, the attention of researchers has again attracted the problem of pregnancy in the presence of scar on the uterus. The aim of the study is to evaluate the processes of myometrium remodeling in women with uterine scar using non-invasive ultrasonic monitoring. It is shown that the frequency of relative failure of yellowing in the uterus does not exceed 2.7% of the total number of women examined. The ratio of the thickness of the residual in the plane of the yellow and normal endometrium indicates complete remodeling and is in women after KP, this index was 0.96 ± 0.08, and after KME - 0.94 ± 0.06 (p> 0.05). The difference in maximum systolic velocity of arterial blood flow in patients after CR (38.8 ±1.2 cm/ s) and after CME (34.2 ±1.4 cm/ sec, p <0.05) can be explained by differences in localization cuts during these surgical interventions . The expediency of using both linear and dopplerometric methods of ultrasound examination in evaluating the ability of rumen on the uterus and myometrium remodeling processes is discussed.